The Determinants of Bank Risk : Case of Tunisia - Mohamed Aymen Ben Moussa (Economics and Business Journal (ECBIS), 2026)
Banks  are  defined  as financial  intermediaries  that borrow  money  from  surplus  spending units and lend to deficit spending units. During this process, they carry out four basic services: liquidity intermediation, denomination intermediation, risk intermediation, and maturity intermediation. The nature of this intermediation makes banks face many risks, including liquidity risk, operational risk, credit risk, interest rate risk and foreign exchange risk. In this study we attempt to identified the determinants of bank risk in Tunisian context . We measured bank risk with (RWTA. NPL and Zscore). We used a sample of 11 banks quoted in financial market of Tunis for the period ( 2014-2023). By estimation of 3 models with the technique of panel data ,we found that liquidity ; total credit ; return on equity ; size ; capital ; economic growth and inflation have a significant effect on bank risk